Pengaruh E-Money terhadap Minat Beli Studi pada Mahasiswa UIN Raden Intan Lampung - Syahputra Amarta, Dhafi; Bimantoro, Jonathan; F. Sanjaya, Vicky (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
At this time, there are many payment models that have been rife among the public, especially among students, which triggers the convenience and convenience, namely E-money. This study aims to find out how much influence on students on the use of E-Money. The method used in this study is the Quantitative approach. The sample used in this study was a collection using primary data. Primary data were obtained using questionnaires or questionnaires. The data analysis used in this study is a simple linear regression test, validity test, hypothesis. The results of the research conducted show that consumer behavior influences the decision to use e-money. E-money has a negative and significant effect on Buying Interest, with a P value of 0.000 more than 0.06.